(NfRANCUZSKAQ MUZYKA PERWOJ POLOWINY hh WEKAs (NISTORIQ (B. (NO^ERKIs - (Ng(B.(NfILENKOs; (Nw(B.(Ns(B.(NbURENKOs (NREDAKTORs ((NlENINGRADs (NmUZYKAs, 1983)
(Nw KNIGI WKL@^ENY ISTORIKO(B-(NANALITI^ESKIE O^ERKI(B.s
Keywords: (NISTORIQs